The Influence of Discipline, Motivation, Local Wisdom, and Work Environment on Employee Performance: The Role of Job Satisfaction as a Mediator - Kopong, Anthoneta; Untajana, Paulus Perey; Lakamudi, Rahma Karnia (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study analyzes the impact of discipline, motivation, local wisdom, and work environment on employee Performance with job satisfaction as a mediator. Discipline and motivation play a significant role in enhancing employee Performance, while local wisdom fosters an atmosphere that supports harmony in the workplace. A conducive work environment also contributes to increased Performance and job satisfaction. The study uses a quantitative survey method involving 465 structural officials in regional work units (OPD). Multiple regression analysis techniques were employed to evaluate the relationships between variables. The findings show that work discipline is positively related to Performance and job satisfaction. Motivation was also found to enhance employee Performance, while local wisdom supports the creation of a better work climate. A positive work environment has a significant effect on both employee satisfaction and Performance. Job satisfaction strengthens the relationship between motivation, local wisdom, and work environment with employee Performance. However, work discipline does not require a mediator to enhance Performance. These findings emphasize the importance of creating a supportive work environment, fostering high motivation, and considering local organizational values to improve Performance.